Structures of Pb-BHA Complexes Adsorbed on Scheelite Surface - Wei, Zhao; Sun, Wenjuan; Hu, Yuehua; Han, Haisheng; Sun, Wei; Wang, Ruolin; Zhu, Yangge; Li, Bicheng; Song, Zhenguo (Frontiers in Chemistry, 2019)
Previous studies have shown that Pb-BHA complexes (lead complexes of benzohydroxamic acid) have better collecting ability and can be used in flotation experiments with BHA acting as a collector and lead ions acting as activators. However, the structures of Pb-BHA complexes adsorbed on a mineral surface remain unclear. In this work, the adsorption behavior of Pb-BHA complexes on the scheelite surface was studied by flotation experiments and adsorption capacity measurements, and the structures of the adsorbed Pb-BHA complexes were determined using X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (TOF-SIMS). The adsorption capacity results showed that more BHA was adsorbed on the scheelite surface in Pb-BHA flotation, and the XPS and TOF-SIMS analysis showed that the species of Pb-BHA complexes adsorbed on the scheelite surface were similar in activation flotation and Pb-BHA flotation. Therefore, the different contents of the complexes on the scheelite surface were responsible for the flotation behavior. XPS and TOF-SIMS showed that BHA combined with lead ions to form complexes with different structures, such as five- and four-membered ring structures. Structure fragment inference based on the measurements indicated that lead ions formed monomer complexes with two BHAs, and that lead hydroxide polymers with a certain degree of polymerization bonded with oxygen atoms in the complexes. The Pb-BHA complexes combine with oxygen atoms on the scheelite surface to form an adsorbate, rendering the surface hydrophobic.